The Language Attitude towards English Learning among EFL Learners: A Case at One Private Islamic Senior High School - Annisa Astrid; Deta Desvitasari; Aghor Aqdam (Ta'dib: Jurnal Pendidikan Islam, 2020)
Attitude is one of the considerable factors in learning and plays an essential role since it can influence language learning and performance. This study aimed at investigating students’ attitudes towards English language learning. Survey method was used in this study to describe the attitudes of the students at one Islamic private senior high school towards English language learning. The participants involved in this study were 217 students at one Islamic private senior high school in Indralaya. In collecting the data, we employed a Likert scale questionnaire consisting of 20 items which were divided into 5 components; (1) attitude towards native English speakers, (2) motivational orientation in learning English, (3) interest in English, (4) attitude towards English class, and (5) attitude towards English teachers. The result of this study indicated that the attitude of the students of one Islamic private senior high school in Indralaya South Sumatera towards English language learning was generally positive.